Emerging technologies in non-destructive testing V : proceedings of the Fifth Conference on Emerging Technologies in NDT, Ioannina, Greece, 19-21 September 2011 /: proceedings of the Fifth Conference on Emerging Technologies in NDT, Ioannina, Greece, 19-21 September 2011. (©2012) - Unknown
No abstract available